Pengaruh Marketing Mix terhadap Keputusan Pembelian di Toko Anik Grosir - Hamzah, Muh; Febriana, Indah Karima (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2025)
This study investigates the influence of the marketing mix, which consists of product, price, place, and promotion, on consumer purchasing decisions at Toko Anik Grosir, a local wholesale store in Tamansari Village, Probolinggo Regency. The main problem addressed is the limited empirical research that examines how each element of the marketing mix affects consumer behavior in small-scale wholesale businesses, particularly in semi-urban or rural settings. This research used a quantitative approach with a descriptive-causal design. Data were collected through purposive sampling involving 96 respondents who had made at least two purchases. The instrument used was a Likert-scale questionnaire, and data analysis was performed using multiple linear regression with SPSS software. The results show that all four variables of the marketing mix simultaneously have a significant influence on purchasing decisions. Partially, product, price, and promotion have a positive and significant effect, while place does not have a significant influence. Among these, the product variable is the most dominant factor influencing consumer decisions. The R Square value of 0.692 indicates that 69.2 percent of the variation in purchasing decisions is explained by the four marketing mix variables. These findings contribute to marketing theory in the retail context and offer practical implications for store owners to improve marketing strategies in competitive local markets.